Intensive Wildfire Associated With Volcanism Promoted the Vegetation Changeover in Southwest China During the Permian−Triassic Transition - Cai, Yao-feng; Zhang, Hua; Feng, Zhuo; Shen, Shu-zhong (Frontiers in Earth Science, 2021)
Palaeo-wildfire, which had an important impact on the end Permian terrestrial ecosystems, became more intense in the latest Permian globally, evidenced by extensive occurrence of fossil charcoals. In this study, we report abundant charcoals from the upper part of the Xuanwei Formation and the Permian–Triassic transitional Kayitou Formation in the Lengqinggou section, western Guizhou Provence, Southwest China. These charcoals are well-preserved with anatomical structures and can be classified into seven distinctive types according to their characteristics. Organic carbon isotopic analyses of both bulk rocks and charcoals show that the δ13Corg values in the Kayitou Formation are notably more negative than those in the Xuanwei Formation, with a negative excursion of 4.08‰ immediately above the volcanic ash bed in the middle of the uppermost coal bed of the Xuanwei Formation. Charcoals with high reflectance values (Romean=2.38%) are discovered below the ash bed. By contrast, the reflectance values (Romean=1.51%) of the charcoals in the Kayitou Formation are much lower than those of the Xuanwei Formation, indicating the palaeo-wildfire types have changed from crown fires to surface fires, which was probably due to the retrogression of vegetation systems during the extinction. Based on the above evidence, we suppose that palaeo-wildfires became more frequent and more severe since the climate became drier during the latest Permian in Southwest China, and the eventual vegetation changeover of the terrestrial ecosystems in Southwest China could be caused by volcanism.